PELAKSANAAN GERAKAN LITERASI BAC PELAKSANAAN GERAKAN LITERASI BACA- TULIS DISEKOLAH DASAR NEGERI 022 MUARA MAHAT BARU - deswita indra (Unit Pelaksana Praktik Kependidikan Terpadu Fakultas Keguruan dan Ilmu Pendidikan Universitas Muhammadiyah Riau, 2023)
This study aims to see what literacy programs are implemented in elementary schools. Schools and teachers foster literacy through the GLS (School Literacy Movement) program. This study aims to see the extent to which literacy literacy programs are implemented in elementary schools. This type of research is a qualitative research with a descriptive approach. The instruments used in this study were interview guides, observations, and documentation. Interviews were conducted with class 1 homeroom teachers where this research was conducted at SDN 022 Muara Mahat Baru. The results of the research show that the program implemented at this school is (1) reading for fifteen minutes (2) reading corner (3) reading in the library or the teacher bringing a reading basket to class which can be done depending on when the teacher applies it. And in implementing literacy programs we need to carry out three stages, namely habituation, development, and learning.